A Body in Fukushima - Johnston, William, 1955-; Johnston, William, 1955-; Otake, Eiko (Book collections on Project MUSE., 2021)
"Haunting color photographs and evocative essays document a decade-long collaboration between performance artist Eiko Otake and photographer and historian William Johnston, who have visited the surreal, irradiated landscapes of post-nuclear meltdown Fukushima, Japan"--